Efficacy decrease of antiviral agents when administered to ongoing hepatitis C virus infections in cell culture - Carlos García-Crespo; Carlos García-Crespo; Lucía Vázquez-Sirvent; Lucía Vázquez-Sirvent; Pilar Somovilla; Pilar Somovilla; María Eugenia Soria; María Eugenia Soria; María Eugenia Soria; Isabel Gallego; Isabel Gallego; Ana Isabel de Ávila; et al. (Frontiers in Microbiology, 2022)
We report a quantification of the decrease of effectiveness of antiviral agents directed to hepatitis C virus, when the agents are added during an ongoing infection in cell culture vs. when they are added at the beginning of the infection. Major determinants of the decrease of inhibitory activity are the time post-infection of inhibitor administration and viral replicative fitness. The efficacy decrease has been documented with antiviral assays involving the combination of the direct-acting antiviral agents, daclatasvir and sofosbuvir, and with the combination of the lethal mutagens, favipiravir and ribavirin. The results suggest that strict antiviral effectiveness assays in preclinical trials may involve the use of high fitness viral populations and the delayed administration of the agents, relative to infection onset.